The European Union's Policy Towards Mercosur Responsive Not Strategic - Arana, Arantza Gomez (European Policy, 2016)
This book provides a distinctive and empirically rich account of the European Union's relationship with the Common Market of the South (Mercosur). It seeks to examine the motivations that determine the EU's policy towards Mercosur; the most important relationship the EU has with another regional economic integration organization. Drawing on extensive primary documents, the book argues that the major developments in the relationship were initiated by Mercosur and supported mainly by Spain. Rather than the EU pursuing a strategy, as implied by most of the existing literature, the EU was largely responsive, which explains why the relationship is much less developed than the EU's relations with other parts of the world.